Infiltration behavior of Cu and Ti fillers into Ti2AlC/Ti3AlC2 composites during tungsten inert gas (TIG)brazing. Issue 3 (15th February 2018) - Chiker, N.; Haddad, A.; Hadji, Y.; Benammar, M.E.A.; Azzaz, M.; Yahi, M.; Sahraoui, T.; Hadji, M.; Barsoum, M.W.
Abstract: Herein we study the infiltration behavior of Ti and Cu fillers into a Ti2 AlC/Ti3 AlC2 MAX phase composites using a TIG-brazing process. The microstructures of the interfaces were investigated by scanning electron microscopy and energy dispersive spectrometry. When Ti2 AlC/Ti3 AlC2 comes into contact with molten Ti, it starts decomposing into TiC x, a Ti-richandTi3 AlC; when in contact with molten Cu, the resulting phases are Ti2 Al(Cu)C, Cu(Al), AlCu2 Ti and TiC. In the presence of Cu at approximately 1630 °C, a defective Ti2 Al(Cu)C phase was formed having a P 63/ mmc structure. Ti3 AlC2 MAX phase was completely decomposed in presence of Cu or Ti filler-materials. The decomposition of Ti2 AlC to Ti3 AlC2 was observed in the heat-affected zone of the composite. Notably, no cracks were observed during TIG-brazing of Ti2 AlC/Ti3 AlC2 composite with Ti or Cu filler materials.